Macroeconomic Shocks and Leverage Effect on Malaysian Islamic Real Estate Investment Trust Stock Return - Choo, William Keng Soon; Mohd Hussin, Mohd Yahya; Muhammad, Fidlizan; Abd. Wahab, Norazlina (Advance Scientific Research, 2020)
Over the past decade, Malaysia’s Islamic capital market is emerging in achieving a total worth of 1.9 million or 61 percent of the overall Malaysian capital market as per December 2018. The establishment of Islamic Real Estate Investment Trust (REIT) gained a demand from investors in the Islamic capital market that claims to be a safe investment as it attached to the real estate to generate the source of income. Nevertheless, the Islamic REITs are structured and operating in accordance with the Shariah principle laid out by the Malaysia securities commission, as it is beneficial to the potential investors given its high liquidity and diversification opportunity compared to investing in physical property. In addition, although Islamic REIT is deemed to have a stable return given the real estate portfolio, there is still risk inherent such as an impact of the external forces. Thus, the impact of macroeconomic factors shocks towards Islamic REITs is significant to the investors, policy makers and government to outline their relationship and facilitate their future growth. However, the evidence published on the listed Islamic REITs stock return in Malaysia is very limited and has seldom been modelled. The Generalized Autoregressive Conditional Heteroscedasticity (GARCH) model and Exponential Generalized Autoregressive Conditional Heteroscedasticity (EGARCH) model would beare employed in this study to analyze the Islamic REIT stock return